California’s community-based tobacco control initiatives: a collaborative approach in the United States - Ekwebene, Onyeka Chukwudalu; Ekwebene, Somto Gibson (International Journal of Research in Medical Sciences, 2024)
California’s Community-Based Tobacco Control Initiatives target smoking incidence through collaboration. Smoking has serious health and economic consequences, stressing the need for concerted action. The California Tobacco Control Program’s smoking reduction success is discussed, focusing on socioeconomic differences. A comprehensive tobacco control strategy should involve multi-sector cooperation, according to the author. The planned collaboration comprises government, private corporations, public and civil society groups, health and social service providers, practitioners, and researchers. The strategy entails building a coalition including the California Department of Health, Community Counselors, Bill and Melinda Gates Foundation, and California Medical Association. The essay discusses coalition issues but also highlights their benefits, such as program capability and awareness.